Sequential Portal Vein Embolization and Percutaneous Radiofrequency Ablation for Future Liver Remnant Growth: A Minimally Invasive Alternative to ALPPS Stage-1 in Treatment of Hepatocellular Carcinoma - Wang, Qiang; Ji, Yujun; Brismar, Torkel B.; Chen, Shu; Li, Changfeng; Jiang, Jiayun; Mu, Wei; Zhang, Leida; Sparrelid, Ernesto; Ma, Kuansheng (Frontiers in Surgery, 2021)
Background: To evaluate the feasibility and efficacy of sequential portal vein embolization (PVE) and radiofrequency ablation (RFA) (PVE+RFA) as a minimally invasive variant for associating liver partition and portal vein ligation for staged hepatectomy (ALPPS) stage-1 in treatment of cirrhosis-related hepatocellular carcinoma (HCC). Methods: For HCC patients with insufficient FLR, right-sided PVE was first performed, followed by percutaneous RFA to the tumor as a means to trigger FLR growth. When the FLR reached a safe level (at least 40%) and the blood biochemistry tests were in good condition, the hepatectomy was performed. FLR dynamic changes and serum biochemical tests were evaluated. Postoperative complications, mortality, intraoperative data and long-term oncological outcome were also recorded. Results: Seven patients underwent PVE+RFA for FLR growth between March 2016 and December 2019. The median baseline of FLR was 353 ml (28%), which increased to 539 (44%) ml after 8 (7-18) days of this strategy (p < 0.05). The increase of FLR ranged from 40% to 140% (median 47%). Five patients completed hepatectomy. The median interval between PVE+RFA and hepatectomy was 19 (15-27) days. No major morbidity ≥ III of Clavien-Dindo classification or in-hospital mortality occurred. One patient who did not proceed to surgery died within 90 days after discharge. After a median follow-up of 18 (range 3-50) months, five patients were alive. Conclusion: Sequential PVE+RFA is a feasible and effective strategy for FLR growth prior to extended hepatectomy and may provide a minimally invasive alternative for ALPPS stage-1 for treatment of patients with cirrhosis-related HCC.